2022
DOI: 10.3168/jds.2021-20990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultra-high pressure treatment on angiotensin-converting enzyme (ACE) inhibitory activity, antioxidant activity, and physicochemical properties of milk fermented with Lactobacillus delbrueckii QS306

Abstract: The present study investigated the influence of ultrahigh pressure (UHP) treatment on angiotensin-converting enzyme inhibitory (ACEI) activity and quality of milk fermented with Lactobacillus delbrueckii QS306 after storage. By varying treatment pressure, duration of pressure treatment, and duration of fermentation, optimal process parameters for the UHP treatment of milk fermented with QS306 to enhance ACEI activity were found to be 400 MPa, 10 min, and 48 h, respectively. The degree of ACE inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This antioxidant activity originates from dadiah, which is used as a raw material for the manufacture of jelly candies. Many previous studies have reported antioxidant activity in probiotic fermented milk [25,26,27]. In general, the antioxidant activity in probiotic fermented milk is due to protein peptides formed during the fermentation process in fermented milk [28,29].…”
Section: Antioxidant Activity and Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…This antioxidant activity originates from dadiah, which is used as a raw material for the manufacture of jelly candies. Many previous studies have reported antioxidant activity in probiotic fermented milk [25,26,27]. In general, the antioxidant activity in probiotic fermented milk is due to protein peptides formed during the fermentation process in fermented milk [28,29].…”
Section: Antioxidant Activity and Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…Among dietary resources, milk protein is considered as an excellent choice to prepare ACE inhibitory peptides via hydrolysis (Wu et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recognized as a potential target for hypertension treatment, the angiotensin-converting enzyme (ACE) is the key enzyme for blood pressure regulation and is mainly localized on the membranes of lungs, heart, kidney, and intestinal cells [ 1 , 2 , 3 ]. The functional balance of ACE is crucial to blood pressure regulation.…”
Section: Introductionmentioning
confidence: 99%